Incidence of functional bi-temporal connections in the human brain in vivo and their relevance to epilepsy surgery. (April 2015) - Jiménez-Jiménez, Diego; Abete-Rivas, Margely; Martín-López, David; Lacruz, María Elena; Selway, Richard P.; Valentín, Antonio; Alarcón, Gonzalo
Abstract: The incidence of functional connections between human temporal lobes and their latencies were investigated using intracranial EEG responses to electrical stimulation with 1 msec single pulses in 91 patients assessed for surgery for treatment of epilepsy. The areas studied were amygdala, hippocampus, parahippocampal gyrus, fusiform gyrus, inferior and mid temporal gyrus. Furthermore, we assessed whether the presence of such connections are related to seizure onset extent and postsurgical seizure control. Responses were seen in any region of the contralateral temporal lobe when stimulating temporal regions in 30 patients out of the 91 (32.96%). Bi-hippocampal or bi-amygdalar projections were seen in only 5% of temporal lobes ( N = 60) and between both fusiform gyri in 7.1% ( N = 126). All other bilateral connections occurred in less than 5% of hemispheres. Depending on the structures, latencies ranged between 20 and 90 msec, with an average value of 60.2 msec. There were no statistical difference in the proportion of patients showing Engel Class I between patients with and without contralateral temporal connections. No difference was found in the proportion of patients showing bilateral or unilateral seizure onset among patients with and without contralateral temporal projections. The present findings corroborate that the functionality of bilateral temporal connections in humans is limited and does not affect the surgical outcome.